PENGARUH SIMPANAN ANGGOTA, PINJAMAN ANGGOTA DAN JUMLAH ANGGOTA TERHADAP SISA HASIL USAHA - Widi Nur Lestari; Bambang Widarno; Sunarti Sunarti (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of member savings, member loansand number of members on the remaining results of operations. The types of dataused in this study are qualitative and quantitative. The data source used issecondary data. The population in this study are all financial statements inSurakarta Civil Servants cooperatives. The sample used in this study is thenumber of member deposits, member loans and the number of members during the2009-2018 period. The sampling technique uses purposive sampling with certaincriteria. The data analysis technique used in this study is multiple linearregression. The results of member savings, member loans and total membershiphave a significant positive effect